Association between expression of TNF-α, P53 and HIF1α with asthenozoospermia. (3rd April 2019) - Ghandehari-Alavijeh, Rana; Zohrabi, Dina; Tavalaee, Marziyeh; Nasr-Esfahani, Mohammad Hossein
Abstract: Reduced sperm motility (asthenozoospermia) accounts for a significant percentage of male infertility and numerous factors have been suggested to explain this phenomenon among which hypoxic and inflammatory markers are the least studied. Therefore, the aim of this study was to assess the main molecular markers involved in hypoxia (P53 and HIF-1α) and inflammation (TNF-α) pathways in infertile men with asthenozoospermia. Expression of these markers were assessed by qRT-PCR, and analysis of data show that mean of hypoxia markers (P53, HIF-1α) and also TNF- α were significantly higher in infertile men with asthenozoospermia compared to fertile men ( p < 0.05). Unlike TNF-α, significant negative correlations were observed between expression of P53 ( r = –0.568; p = 0.002) and HIF-1α ( r = –0.403; p = 0.046) with sperm motility. In addition, a significant negative correlation was observed between expression of P53 with sperm concentration ( r = –0.576; p < 0.001). In addition, a significant positive correlation was observed between hypoxia markers (P53, HIF-1α) and TNF-α ( p < 0.01). However, no significant relation was observed between TNF-α and semen parameters. Taken together, the results of this study suggest the involvement of hypoxia pathway is more pronounced than the inflammatory pathway in asthenozoospermia.